Vascular access for incident hemodialysis patients in Catalonia: analysis of data from the Catalan Renal Registry (2000-2011). Issue 6 (November 2015) - Roca-Tey, Ramon; Arcos, Emma; Comas, Jordi; Cao, Higini; Tort, Jaume; ,
Purpose: Arteriovenous fístula is the best vascular access (VA) for hemodialysis. We analyzed the VA used at first session and the factors associated with the likelihood to start hemodialysis by fistula in 2000-2011. Methods: Data of VA type were obtained in 9, 956 incident hemodialysis patients from the Catalan Registry. Results: Overall, 47.9% of patients initiated hemodialysis with a fistula, 1.2% with a graft, 15.9% with a tunneled catheter and 35% with an untunneled catheter. The percentage of incident patients with fistula and catheter has remained stable at around 50% over the years. The likelihood to start hemodialysis with fistula was significantly lower in females [adjusted odds ratio: 0.69, 95% confidence interval (CI): 0.61-0.75], patients aged 18-44 years (0.78, 95% CI: 0.64-0.94), patients with comorbidity (0.67, 95% CI: 0.60-0.75) and tended to be lower in patients aged over 74 years (0.89, 95% CI: 0.78-1.01). The probability to use fistula was significantly higher in patients with polycystic kidney disease (2.08, 95% CI: 1.63-2.67), predialysis nephrology care longer than 2 years (4.14, 95% CI: 3.63-4.73) and steady chronic kidney disease (CKD) progression (10.97, 95% CI: 8.41-14.32). During 1 year of follow-up, 67.2% and 59.6% of patients using untunneled and tunneled catheter changed to fistula, respectively. Conclusions: Starting hemodialysis by fistula was related with nonmodifiable patient characteristics and modifiable CKD practice processes, such as predialysis care duration. Half of the incident patients were exposed annually in Catalonia to potential catheter complications. This scenario can be improved by optimizing the processes of CKD care.